Influence of organic and inorganic sources of nutrients on growth and yield of rice in Tarai region of Uttarakhand - Jeet, Indra; Pandey, P.C.; Singh, Gagan Deep; Shankhwar, Anil Kumar (Annals of Agricultural Research, 2014)
The present paper deals with the effect of organic and inorganic sources of nutrient on growth and yield of rice in rice-wheat cropping system. The field experiment was conducted at the Norman E.Borlaug Crop Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar, U.S. Nagar, Uttarakhand, India on mollisol. Green manuring of Sesbania rostrata (SR) (42.8 t/ha green fresh biomass at 60 days stage) with FYM (5 t/ha) produced significantly higher grain yield (6.5 t/ha) than other treatments except FYM 10 t, N180P60K40 and N200P60K40. These treatments also producedsignificantly higher biological yield than recommended dose of fertilizer (N120P60K40). The different treatments were found to have significant bearing effect on height and dry matter accumulation. Dry matter accumulation at maximum tillering stage was highest with FYM + SR and significantly higher than all treatments except SA + N0P60K40 and N200P60K40. The significant result were showed by the use of organic sources i.e. Sesbania rostrata green manuring with FYM 5 t, FYM 10 t and integrated Â use of N120P60K40 + straw burned and SA + N0P60K40 in rice in intensive rice-wheat cropping system.